AKTIVITAS MAHASISWA DI LUAR KAMPUS DALAM UNGKAP KARYA SENI LUKIS KONTEMPORER - ANDRES PERMADI, Drs. Idran Wakidi, Yasrul Sami, S.Sn., M.Sn (Universitas Negeri Padang, 2015)
Students have the role and function in society are growing. Student mustpossess responsibility, skilled and hardworking between lectures with off-campus activities. Activity outside the campus has many varieties, such as working as an employee or self-employed as well, following the organization's activities, hobbies, and develop the skills possessed. College while working or other activities outside the campus is a new alternative to train independence, adds to the experience, as well as other science that can deliver a step in the era of contemporary society. From Students like is what lies behind the writer to put it on the painting with the title